Recovery of ZnO and Cu from Brass Smelter Slag by Hydrometallurgy Process. - Nguyen, Thi Thao; Nguyen, Duc Trung; Dinh, Thi Hinh; Tran, Vu Diem Ngoc (JST: Engineering And Technology For Sustainable Development, 2022)
Vietnam has many traditional copper casting craft villages from the North to the South, which resulting in large amounts of copper smelter slag containing Zn, Cu, Al, etc. In this study, zinc oxide and copper metal have been successfully recovered from brass smelter slag (71.80 wt.% ZnO and 10.32 wt.% CuO) by a hydrometallurgical process. The brass smelter slag was leached in sulfuric acid with a concentration of 125–225 g/L H2SO4 at a leaching temperature of 30–70 ºC for 30–120 min. The extraction percentage of Cu and ZnO was obtained at 80.26% and 81.71%, respectively. The optimal leaching condition was determined as 175 g/L H2SO4 at 50 ºC for 90 min. The leaching solution was purified by removing Fe, Mn and Al, etc. via oxidizing the ion Fe2+ to Fe3+ and having a pH of 5.5. The solution was continuously cemented by Zn metal at 60 oC for 60 min to obtain Cu metal with a high purity of 99.22 wt.% Cu. The solution purification with 85.43 g/L Zn was adjusted to a pH value of 8-8.5 to precipitate zinc hydroxide Zn(OH). The precipitation was calcinated at 600 ºC for 120 min to obtain ZnO (97.19 wt.%). The recovery of copper and zinc has become crucial due to the increasing prices of these metals and environmental factors involved.